Seroepidemiology and Molecular Detection of Brucellosis among Pakistani Women with Spontaneous Abortions - Ali, Afzal; Mobeen, Hifsa; Bibi, Azeem; Rafiq, Insha; Fatima, Asma (Indus Journal of Bioscience Research, 2025)
Background: Brucellosis is a major public health hazard, especially in tropical and subtropical regions. The disease poses a considerable hazard because of its quick transmission and the possibility of severe sequelae. Objective: This study aims to determine the seroepidemiology and molecular detection of brucellosis among Pakistani women with spontaneous abortion. Methodology: A cross-sectional study was conducted in different hospitals of Lahore over four months. A total of 165 abortion cases were investigated for brucellosis using a sequential diagnostic approach involving the Rose Bengal Plate Test (RBPT), Enzyme-Linked Immunosorbent Assay (ELISA), and Polymerase Chain Reaction (PCR). Results: Initial screening with RBPT identified 41 (24.84%) positive cases, while 124 (75.15%) were negative. The RBPT positive samples were further evaluated by ELISA, which confirmed 34 (82.9%) as positive and 7 (17.0%) as negative. Subsequently, PCR analysis of the 34 ELISA-positive samples revealed 27 (79.4%) were positive for Brucella DNA, whereas 7 (20.5%) were PCR-negative. Conclusion: These findings indicate a confirmed brucellosis prevalence of 16.36% (27/165) among the abortion cases, underscoring the importance of combining serological and molecular diagnostics for accurate detection of Brucella infection.